Growth and longevity of the spider crab Libinia ferreirae (Majoidea, Epialtidae) - Lemos Goncalves, Geslaine Rafaela [UNESP]; Miazaki, Lizandra Fernandes [UNESP]; Bolla Junior, Eduardo Antonio [UNESP]; Grabowski, Raphael Cezar [UNESP]; Costa, Rogerio Caetano da [UNESP]; Castilho, Antonio Leao [UNESP] (Soc Brasileira Carcinologia, 2020)
We estimated the growth parameters of the spider crab, Libinia ferreirae (age, asymptotic size and growth rate) using the von Bertalanffy growth equation model. We obtained nine cohorts for female carapace asymptotic width (CW infinity) = 64.32 mm, growth coefficient (day(-1)) (k) = 0.0027 e t(0) = 0.77 days) and seven for males (CW infinity = 81.93 mm, k= 0.0021 e t(0) = 0.49 days). The longevity for males was higher than that for females, estimated 2,156 days (5.91 years) and 1,706 days (4.68 years), respectively. The growth curves for males and females differed (F = 34.67 e p < 0.001). Males reached gonadal maturity before morphometric maturity and occurred at 8.8 and 16.6 months of life, respectively. Females reach gonad and morphometric maturity synchronously and this was estimated to occur at about 11.42 months of life. These crabs invest a great amount of energy in growth during a brief period of their development until reaching the terminal moult. This growth strategy would bring less wear to the organism and consequently a greater longevity.
Keywords: Growth; von Bertalanffy; puberty moult; age; symbiotic relationship